THE INFLUENCE OF DUE PROFESSIONAL CARE, AUDIT ETHICS, AND INDEPENDENCE ON AUDIT QUALITY AT THE REGIONAL INSPECTORATE OF EAST NUSA TENGGARA PROVINCE - Tiffany N.P. Gah (Jurnal Ekonomi, 2023)
This study aims to see whether there is an influence between Due Professional Care, Audit Ethics, and Independence on Audit Quality. The data in this study were obtained from distributing questionnaires at the office of the Regional Inspectorate of the Province of NTT. The analytical method used is multiple linear analysis to see the effect between variables. The results of this study indicate that Due Professional Care, Audit Ethics, and Independence have a significant influence on audit quality, with significant values for Due Professional Care of 0.017 , Audit Ethics of 0.030, and Independence of 0.010.